Environmental Policy in General Equilibrium: When the Choice of Numeraire Matters - Cloé Garnache; Pierre Mérel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper derives the incidence of a pollution tax in a stylized general equilibrium framework, building on previous work by Fullerton and Heutel (2007a). Using the CPI as numeraire, we show that tax incidence is a simpler problem than previously thought, and that general insights can be derived without the need to restrict the parameter space. In addition, the counter-intuitive possibility that an increase in the tax could lead to worse pollution outcomes vanishes. The choice of the CPI as numeraire is further justified by the fact that environmental taxes, for instance carbon taxes, are typically indexed on inflation.
Keywords: Q52; H23; H22; 330; tax incidence; general equilibrium; relative prices; numeraire